Attention and skepticism to greenwashing: analysis of influence on consumer behavior - Andreoli, Taís Pasquotto; Minciotti, Silvio Augusto (Revista de Administração da UFSM, 2023)
Purpose: The goal was to assess the influence of greenwashing on consumer behavior, according to the levels of attention and skepticism involved in receiving and processing the stimulus. Design/methodology/approach: The method consisted of a hypothetical-deductive approach, performed through an experiment (n=151) with a 2 (attention or pre-attention) x 2 (skepticism or non-skepticism) factorial design, with the presentation and subsequent evaluation of a fictional advertising image with greenwashing. Findings: It was observed that the situation of greater consumer criticality occurred with the presence of both attention and skepticism, the opposite also being true, that is, lesser criticality (or greater vulnerability) of consumer was detected when both attention (pre-attention) and skepticism were absent. These results were found in the three investigated variables: green associations, image evaluation, and judgment about the greenwashing practice. Research implications: It has, as a contribution, not only the investigation of fairly unexplored constructs but also the combination and study in a connected way, bringing to the discussion the cognitive processes involved in the reception, processing, registration, and recovery of stimuli, especially in relation to the process of attention, and linking them to the practice of greenwashing. Practical implications: Managing implications can be seen from three main perspectives: organization, consumers, and government, all related to the importance and need for greater awareness. Originality/value: The study provided an unprecedented understanding of the role of two important cognitive processes (attention and skepticism) in consumer behavior in reaction to the practice of greenwashing.